Managing Brazilian Football Clubs: Alternative Sources of Income - Silva, Cláudio Vicente Di Gioia Ferreira (2009)
Football as a business is a chance of socio economic leverage. Football organizations need to become modern since the Brazilian society is unhappy with the quality of service provide and clubs, mostly emerged on debts, end up devaluating their brands associated with an inefficient administration. In 1998, a new factor came to influence this scenario: it was sanctioned the Law no. 9.615, know as “Lei Pelé”, which extinguished the pass of football players. Before that, football clubs have as their major income source the transfer of players. After this regulatory change, clubs were obligated to develop alternative sources of income. The current article intends to analyze this new scenario and to propose options to the clubs not only related to the players transfer market. To do that, it will be shown a comparative study between the Brazilian football and the European Football, identifying the strategies and the results. In this context, public support and the relation between clubs and their clients appeared as the major items.